Molecular Mechanisms Involved in Interleukin-1β Release by Macrophages Exposed to Metal Ions from Implantable Biomaterials - Ferko, Maxime-Alexandre (Université d'Ottawa / University of Ottawa, 2018)
Metal ions released from implantable biomaterials have been associated with adverse biological reactions that can limit implant longevity. Previous studies have shown that, in macrophages, Co2+, Cr3+, and Ni2+ can activate the NLR family pyrin domain-containing protein 3 (NLPR3) inflammasome, which is responsible for interleukin(IL)-1β production through caspase-1. Furthermore, these ions are known to induce oxidative stress, and inflammasome priming is known to involve nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling. However, the mechanisms of inflammasome activation by metal ions remain largely unknown. The objectives of this thesis were to determine if, in macrophages: 1. IL-1β release induced by metal ions is caspase-1-dependent; 2. caspase-1 activation and IL-1β release induced by metal ions are oxidative stress-dependent; and 3. IL-1β release induced by metal ions is NF-κB signaling pathway-dependent. Lipopolysaccharide (LPS)-primed murine bone-marrow-derived macrophages were exposed to Co2+, Cr3+, or Ni2+, with or without an inhibitor of caspase-1, oxidative stress, or NF-κB. Culture supernatants were analyzed for active caspase-1 (immunoblotting) and/or IL-1β (ELISA). Overall, results showed that while both Cr3+ and Ni2+ may be inducing inflammasome activation, Cr3+ is likely a more potent activator, acting through oxidative stress and the NF-κB signaling pathway. Further elucidation of the activation mechanisms may facilitate the development of therapeutic approaches to modulate the inflammatory response to metal ions, and thereby increase implant longevity.
Keywords: bioengineering; biomedical engineering; biomaterials; biocompatibility; orthopaedics; implants; metal alloys; metal ions; adverse tissue reactions; immune response; inflammation; molecular mechanisms; inflammasome activation; NLRP3; NALP3; macrophages; bone marrow-derived macrophages